MIGRASI AUSTRONESIA DAN IMPLIKASINYA TERHADAP PERKEMBANGAN BUDAYA DI KEPULAUAN INDONESIA - Noerwidi, Sofwan (AMERTA, 2014)
Abstrak. Pada saat masyarakat penutur bahasa Austronesia datang di Kepulauan Indonesia, kawasan ini bukanlah suatu daerah kosong tidak berpenghuni. Beberapa pulau di Kepulauan Indonesia telah dihuni oleh populasi lain. Akibat adanya kontak antar-komunitas tersebut mengakibatkan proses adaptasi, inovasi, dan interaksi budaya yang khas sebagaimana tercermin pada perkembangan teknologi alat kerang, teknologi pelayaran dan domestikasi hewan yang dikuasai masyarakat penutur bahasa Austronesia. Tahapan proses migrasi masyarakat penutur bahasa Austronesia di Kepulauan Indonesia dapat dirangkum sebagai berikut: terjadi intrusi budaya baru di Kepulauan Indonesia yang dibawa oleh Austronesia. Akibat dari peristiwa tersebut, terjadi perkembangan budaya Neolitik di Kepulauan Indonesia, disebabkan oleh adaptasi, evolusi dan interaksi antara masyarakat pendatang Austronesia dengan komunitas Non-Austronesia yang telah menghuni kawasan ini sejak masa sebelumnya. Interaksi antar-budaya yang intensif menyebabkan integrasi budaya Austronesia dan Non-Austronesia di Kepulauan Indonesia. Kata Kunci: Migrasi-Kolonisasi, Austronesia, Kepulauan Indonesia, Adaptasi budaya. Abstract. Austronesian Migration and Its Implication on Cultural Development in Indonesian Archipelago. When Austronesian language speakers came to Indonesian Archipelago, this region is not an empty place but had already inhabited by other population. The unique processes of adaptation, innovation, and culture interaction of Austronesian people in this new region are reflected on the development of shell tool technology, navigation technology, plant cultivation and animal domestication. In summary, the stages of Austronesian migration in Indonesian Archipelago are as follows: Intrusion of a new culture that was brought to the Indonesian Archipelago by the Austronesian people, which caused innovation of Neolithic culture in Indonesian Archipelago due to cultural adaptation, evolution, and interaction between the Austronesian speakers (the newcomers) with the indigenous Non-Austronesian communities. Intensive inter-cultural interactions have created a cultural integration between the Austronesians and Non-Austronesians in the Indonesian Archipelago. Keywords: Migration, Austronesian people, Indonesian archipelago, Cultural adaptation.